Role of ICT in the innovation process based on firm-level evidence from four ASEAN economies: An SEM approach - Hiroki Idota; Yasushi Ueki; Teruyuki Bunno; Sobee Shinohara; Masatsugu Tsuji (International Telecommunications Society (ITS), 2014)
Although the East Asian economies have been developing in the 21th century, innovation is indispensable for their further economic development. In order to achieve successful innovation, firms have to elevate their capability including technology, human resources, business organization, ICT use and so on by collaborating with outside organizations such as MNCs (Multi-national companies), universities, public organizations. The outside organizations are termed as external linkages. Based on authors' survey data of four ASEAN economies such as Vietnam, Indonesia, the Philippines, and Thailand from 2012 to 2013, this paper examines how factors such as organizational learning, ICT use, and technology enhance product and process innovation. These factors are used as latent variables in analysis and consist of the following variables: (i) technology such as capital goods, (ii) organizational learning including QC, cross-functional teams, (iii) ICT use such as B2B, B2C, EDI, SCM, ERP, CAD/CAM, groupware, SNS etc., and (iv) external linkages, such as MNCs, local and public organizations, and universities. This study employs SEM (Structural equation modeling) in order to analyze the causal relationships not only among the above four latent variables but also between these and innovation. The six hypotheses were postulated as follows: H1. External linkages enhance organizational learning; H2. External linkages improve capital goods; H3. External linkage improves ICT use; H4. Organizational learning improves capital goods; H5. Organizational learning improves ICT use; and H6. Organizational learning, ICT use, and capital goods enhance innovation. Estimation results on product innovation demonstrate that organization learning, technology (capital goods), and ICT use enhance product innovation. On the other hand, organization learning promotes technology (capital goods) and ICT use, which promotes process innovation. Accordingly, this study clarifies that ICT use, technology and innovation capability enhance product and process innovation.
Keywords: 330; ICT use; innovation; internal capability; external linkages; SEM (Structural equation modeling)